Total Synthesis of the 7, 10‐Epimer of the Proposed Structure of Amphidinolide N, Part I: Synthesis of the C1–C13 Subunit. Issue 10 (4th February 2016) - Ochiai, Koji; Kuppusamy, Sankar; Yasui, Yusuke; Okano, Tsubasa; Matsumoto, Yasunobu; Gupta, Nishant R.; Takahashi, Yohei; Kubota, Takaaki; Kobayashi, Jun'ichi; Hayashi, Yujiro
Abstract: Amphidinolide N, the structure of which has been recently revised, is a 26‐membered macrolide featuring allyl epoxide and tetrahydropyran moieties with 13 chiral centers. Due to its challenging structure and extraordinary potent cytotoxicity, amphidinolide N is a highly attractive target of total synthesis. During our total synthesis studies of the 7, 10‐epimer of the proposed structure of amphidinolide N, we have synthesized the C1–C13 subunit enantio‐ and diastereoselectively. Key reactions include anl ‐proline catalyzed enantioselective intramolecular aldol reaction, Evans aldol reaction, Sharpless asymmetric epoxidation and Tamao–Fleming oxidation. To aid late‐stage manipulations, we also developed the 4‐( N ‐benzyloxycarbonyl‐ N ‐methylamino)butyryl group as a novel ester protective group for the C9 alcohol. Abstract : Recent revision : Amphidinolide N, the structure of which has been recently revised, is a 26‐membered macrolide featuring allyl epoxide and tetrahydropyran moieties with 13 chiral centers. Due to its challenging structure and extraordinary potent cytotoxicity, amphidinolide N is a highly attractive target of total synthesis. During the total synthesis studies of 7, 10‐ epi ‐amphidinolide N, the C1–C13 subunit was synthesized enantio‐ and diastereoselectively .